ISLAMIC CULTURE AND THE MENTALITY FORMED ON ITS BASIS IN TURKESTAN IN THE LATE XIX AND EARLY XX CENTURIES - Zakir Rustamov (Western European Studies, 2024)
The article is devoted to the analysis of some aspects of the Islamic society of Turkestan on the eve of the invasion of the Russian Empire. The Russian invasion took place at a time when the Islamic society in Turkestan was going through a crisis. The author tries to reveal the historical reasons of this process, to justify the need for reforms in Turkestan society. According to the author, Islamic fanaticism, its closedness to debates and doubts had an impact on the social and political life in Turkestan, on the mentality of the peoples here, and became one of the reasons for the backwardness and ignorance, as a result of the Russian invasion.
Keywords: Russia; Turkestan; empire